Caracterização agronômica de linhagens de pimentão (Capsicum annuum L.) - Tavares, Rafael Dantas Asbahr (Universidade Federal de São Carlos, 2023)
Bell peppers are a popular vegetable in many cuisines around the world, known for their versatility and flavor. It is an excellent source of nutrients, including vitamins A and C, as well as containing fiber and antioxidants. Generally, the bell pepper market tends to be stable, with consistent demand due to its use in many culinary dishes around the world. However, prices and supply may vary depending on the region and growing season. Factors such as weather conditions, pests and diseases can also affect the production and availability of peppers in certain areas. Agronomic characterization provides useful information for the selection of lines developed in genetic improvement programs. The purpose of the present study was the agronomic characterization of pepper (Capsicum annuum) strains, with the aim of providing crucial information for the selection of strains aligned with production goals and market preferences. Six pepper lines (F511357, F511361, F511362, F511363, F511365, F51366) were evaluated in a protected environment, following a randomized block design (DBC) with 6 treatments and 3 replications, where each of the lines had 9 pots. Each strain was evaluated for its biometric characteristics, production and qualitative parameters. The results obtained revealed important differences between the strains, highlighting some of them due to their desirable characteristics, such as larger fruit size and pulp thickness, productivity. The study has undesirable characteristics, such as the presence of streaks in the fruits and anthocyanin, which affect the fruit ripening process. Therefore, the study contributed significantly to knowledge on the subject, offering a basis for making decisions when choosing the best pepper lines, which were the F511357 and F511361 lines due to the best fruit characteristics sought by the market linked to good productivity. Furthermore, the research expanded the understanding of the genetic diversity present in the strains studied, playing a fundamental role in the context of the genetic improvement of this crop.
Agronomic characterization of pepper lines (Capsicum annuum L.)
Keywords: Características biométricas; Melhoramento genético; Parâmetros qualitativos; Produção; Seleção; Biometric characteristics; Production; Selection; Qualitative parameters; Genetic improvement; CIENCIAS AGRARIAS::AGRONOMIA